Analisis dan Perancangan E-Learning Adaptif di Sekolah Menengah Kejuruan - Winna Dharmayanti; Ratih Widya Nurcahyo (Universitas Hamzanwadi, 2021)
Schools have not taken advantage in using technology to carry out online-based learning 4.0, though schools have computer laboratories and Internet networks. Teachers and students need e-learning media (ELM) that can be used in learning outside the classroom. The aim of this study is to analyze and design adaptive of ELM according to the needs of teachers and students at SMK Mandiri. The purpose of this study is to study to examine and to design of ELM in accordance with what is needed by teachers and students at SMK Mandiri. The method used in this research is R D method apply ADDIE model by analyzing and designing stages only. The subjects of this development research were media expert and e-learning system expert. Data collection used is direct and indirect communication techniques, which is done virtually to determine the needs of teachers and students and questionnaire to determine the level of product feasibility. The results of this study indicate that there is a need for ELM-adaptive and designs at SMK Mandiri. The conclusion from this research is to analyze the ELM-adaptive, which can display three styles of student learning styles, namely, visual, auditory and kinesthetic, then designing and create a flow cart to describe ELM.